Teaching the Future Teachers: A Teacher Educator’s Self-Study in Making Science Relevant, Useful and Meaningful for New Zealand Pre-Service Teachers - Steven Sexton (Journal of Education in Science, Environment and Health)
This self-study investigated how one teacher educator influenced his final-year pre-service teachers perceived primary science classroom learning environment. The study utilized the Nature of Science as Argumentative Questionnaire (NSAAQ) and regularly scheduled focus group interviews. These tools investigated how the learning environment the teacher educator created effectively modelled the pedagogical approaches stated in The New Zealand Curriculum. The initial NSAAQ results indicated where the pre-service teachers understanding of the nature of science were naïve and what aspects needed to be addressed over the course of the programme. Focus group sessions revealed how some of the student teachers’ science attitudes altered over their course of study. These pre-service teachers reported they are now more confident to teach science and that their teacher educator influenced their anticipated teaching practices. This research supports the importance of self-study in initial teacher education.